Management and Security in the Age of Hyperconnectivity 10th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2016, Munich, Germany, June 20-23, 2016, Proceedings - Badonnel, Rémi; Koch, Robert; Pras, Aiko; Drašar, Martin; Stiller, Burkhard (Computer Communication Networks and Telecommunications, 2016)
This book constitutes the refereed proceedings of the 10th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2016, held in Munich, Germany, in June 2016. The 7 full papers presented together with 3 short papers were carefully reviewed and selected from 22 submissions. The volume also includes 9 papers presented at the AIMS PhD workshop. They were reviewed in a separate process and selected from 21 submissions. The full papers are organized in topical sections on autonomic and smart management and security attacks and defenses. The workshop papers are organized in topical sections on management of future networks and security management. The short papers deal with methods for management and security.